"So-called influencers": Stancetaking and (de)legitimation in mediatized discourse about social media influencers. (October 2022) - Droz-dit-Busset, Olivia
Abstract: As contemporary wordsmiths and new-generation copywriters, Social Media Influencers (henceforth SMIs) are inherently germane to critical sociolinguistics. Interested in wider cultural discourses about contemporary forms of 'independent' language work, this paper examines English-language news media representations of SMIs. The empirical focus of my analysis is a dataset of 143 news stories collected from major 'broadsheet' newspapers and LexisNexis. Specifically, I identify two contradictory stances – celebration and derision – by which SMIs are popularly framed. It is in this way, and following van Leeuwen (2007), that their cultural status and work is (de)legitimized. Using the legitimation tactics of theoretical rationalisation and mythopoesis, celebratory stances in my data construct SMIs as a perfect fit for today's ideal of entrepreneurial success – as ambitious, self-optimizing and risk-taking individuals – ultimately contributing to the recasting of independent and sometimes precarious employment as aspirational 'entrepreneurship'. Conversely, derisory stances built on the legitimation tactics of moral evaluation and authorisation lament their lack of work ethic as well as their interloping into industries that do not want them. Thus, the news media appear to both applaud SMIs for their entrepreneurial careers and be vested in sanctioning them for foregoing gatekeepers by not following traditional career paths to stable employment. Ironically, and perhaps even hypocritically, the latter are precisely the kind of employment that are increasingly difficult for many young people to access while the former still prerequisite considerable privilege to be able to pursue.